2022
DOI: 10.3390/w14233922
|View full text |Cite
|
Sign up to set email alerts
|

Climate Changes and Hydrological Processes

Abstract: Due to the influences of climate changes and human activities, extreme climate events have made obvious changes to the hydrological process and the temporal-spatial distribution of water resources over the past several decades [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…(14) have reported that over 70% of the world's drylands are found in developing countries where inhabitants already face critical challenges related to poverty and food insecurity. In spite of their constraints by water scarcity and high sensitivity to climate change and variability brought about by their extreme ambient temperatures, and with extremes such as droughts and floods projected to intensify, drylands still play a major role globally as they occupy over 41% of the global terrestrial area and support nearly 40% of the world's population, 90% of who live in the developing countries (15,16). Drylands all over the world are known for forage production, making pastoralism a major livelihood activity in these areas.…”
Section: Introductionmentioning
confidence: 99%
“…(14) have reported that over 70% of the world's drylands are found in developing countries where inhabitants already face critical challenges related to poverty and food insecurity. In spite of their constraints by water scarcity and high sensitivity to climate change and variability brought about by their extreme ambient temperatures, and with extremes such as droughts and floods projected to intensify, drylands still play a major role globally as they occupy over 41% of the global terrestrial area and support nearly 40% of the world's population, 90% of who live in the developing countries (15,16). Drylands all over the world are known for forage production, making pastoralism a major livelihood activity in these areas.…”
Section: Introductionmentioning
confidence: 99%
“…Changes in land use tend to alter land surface cover which has a significant influence on the catchment hydrology (12). Pressure on land resources for purposes of providing food, water, and shelter to the ever-growing human population has brought about notable changes in LULC with corresponding impacts on hydrological regimes of watershed areas (13)(14)(15)(16)(17)(18)(19). Among the most notable LULC changes that impact a catchment's surface water yield is deforestation; the permanent alteration of a forest to another on-forest use such as agriculture or urban development (20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Hydrological models are effective tools for flood simulation, including lumped hydrological models and distributed hydrological models [5][6][7]. The lumped hydrological model regards the basin as a whole and calculates the hydrological processes such as precipitation, evaporation, and infiltration on the surface of the basin.…”
Section: Introductionmentioning
confidence: 99%